The The Impact of Artificial Intelligence on Health Literacy of Surgical Patients: A Literature Review - kurt alkan, tÃ¼lin (Talenta Publisher, 2025)
This literature review was conducted to evaluate studies assessing the impact of artificial intelligence on the health literacy of surgical patients. A systematic search of the PubMed, Science Direct, Taylor & Francis, and Google Scholar databases, as well as the National Academic Network and Information Center, was performed. The search was limited to articles published in English or Turkish in the last five years, using the following keywords such as